INOVASI PEMBELAJARAN IPS MELALUI MODEL TEAM GAME TOURNAMENT (TGT) BERBANTUAN QUIZIZZ UNTUK MENINGKATKAN KETERAMPILAN SOSIAL SISWA - Wawan Gunawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The development of digital technology and globalization has driven the transformation of learning towards a more interactive, collaborative, and student-centered process. However, social studies learning in schools is still often considered boring, abstract, and less able to improve students' social skills. Low student learning motivation and the dominance of conventional media such as Microsoft PowerPoint are challenges in creating effective learning. This study aims to analyze the effect of the Team Game Tournament (TGT) Cooperative Model assisted by Quizizz media on students' social skills, the effect of learning motivation on students' social skills, and the interaction between learning models and learning motivation in social studies learning at SMPN 2 Ketapang. The study used an experimental method with a Nonequivalent Control Group Design and a 2x2 factorial design. The research sample consisted of 121 ninth-grade students in the 2024/2025 academic year who were divided into experimental and control groups using saturated sampling techniques . Data collection was carried out through social skills tests, learning motivation questionnaires, observation, and documentation. Data analysis used normality tests, homogeneity tests, and two-way ANOVA assisted by SPSS 27.0. The results of the study indicate that the TGT learning model assisted by Quizizz has a significant effect on students' social skills compared to the use of Microsoft PowerPoint with an F value of 139.709 and a significance of 0.000. Learning motivation also has a significant effect on students' social skills with an F value of 10.512 and a significance of 0.002. In addition, there is a significant interaction between the learning model and learning motivation on students' social skills with an F value of 11.250 and a significance of 0.001. The findings of the study indicate that cooperative learning assisted by interactive technology is able to create a more active, competitive, and collaborative learning atmosphere so that it effectively improves students' social skills. The implications of this study emphasize the importance of integrating interactive digital learning media in social studies learning to support the development of students' social skills and learning motivation. Further research is recommended to test the effectiveness of similar models at different educational levels and develop other variables such as communication skills, creativity, and cognitive learning outcomes.